Multinational Firms and the Regulatory Framework in Brazil (1951-1967) - De Campos, Fábio Antonio (2015)
Taking into account the significant number of new multinational companies that entered Brazil in the 1950s, the objective of this paper is to present the main mechanisms of state regulation of international investment and profit remittances during the stage of industrialization that took place between the second Vargas government (1951-1954) and the beginning of the military dictatorship (1964-1967). This was a period in which multinationals had considerable influence on the internal deployment of productive forces. The study focuses on discontinuities in the government’s institutional arrangements related to international capital. The analysis concentrates primarily on two questions: i) was the association with international capital during Kubitschek’s government really a rupture with the development strategy proposed by the second Vargas government?; ii) what was the essence of the most important changes in Brazilian productive internationalization following the economic reforms that were implemented as soon as the military regime took power in 1964?